The Hadith on Purifying Dog Licks: In Search of the Authenticity from Scientific Perspective - Ahmad , Arifuddin; Mahmud , Amir (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
The Prophet tradition, which explains on how to purify a vessel licked by a dog, has a different editorial (text) and substance (content). This difference gives the impression that the Prophet is showing inconsistencies in giving teaching to his companions, which results in confusion for the next generation in understanding the hadith. To examine the truth of the hadith, the researcher aims at locating two standard methods in the study of the hadith that are to examines the chains (sanad) and content (matn). By these two methods, the validity of the hadith can be considered for its authenticity. Besides, scientific evidence by examining the saliva content of dogs could be an alternative way to prove the truth of the h}adi>th. It argues that the truth of the various hadith is in line with that of scientific research. The saliva of a pet can be cleaned by seven times of water rinse. While seven rinses of water can clean the saliva of wild dogs, and one of them should be mixed with soil.